Surge-Resistant Nanocomposite Enameled Wire Using Silica Nanoparticles with Binary Chemical Compositions on the Surface. (18th November 2015) - Yoo, Jeseung; Kim, Yongbeom; Kwon, Suyong; Lee, Joohyun; Seo, Young-Soo
Abstract : We developed polyesterimide (PEI) nanocomposite enameled wires using surface-modified silica nanoparticles with binary chemical compositions on the surface. The modification was done using silanes assisted by ultrasound, which facilitated high density modification. Two different trimethoxysilanes were chosen for the modification on the basis of resemblance of chemical compositions on the silica surface to PEI varnish. The surface-modified silica was well dispersed in PEI varnish, which was confirmed by optical observation and viscosity measurement. The glass transition temperature of the silica-PEI nanocomposite increased with the silica content. The silica-dispersed PEI varnish was then used for enameled wire fabrication. The silica-PEI nanocomposite enameled wire exhibited a much longer lifetime compared to that of neat PEI enameled wire in partial discharge conditions.